Effects of metakaolin on a novel aerated magnesium phosphate cement with high early strength. (30th October 2018) - Yi, Gao; Ma, Cong; Long, Guangcheng; Zhao, Bin; Xie, Youjun
Highlights: A novel porous material with high early strength is prepared at standard curing condition. Metakaolin can improve the strength and water resistance of aerated MPC significantly. Aerated MPC with metakaolin has a more homogeneous pore structure with more finer pores. Abstract: Magnesium phosphate cement (MPC) was proved to be a cementitious material for preparing porous materials with high early-stage strength under standard curing condition. However, the poor water resistance of MPC-based porous materials limits the further application. This study employs metakaolin to improve the performance of aerated MPC. Testing results indicate that the presence of metakaolin produces more finer pores which makes the pore structure more homogeneous. For this reason, metakaolin improves both the compressive strength and water resistance with little negative impact on the thermal insulation property of aerated MPC. The metakaolin modified aerated MPC with a density of about 650 kg/m 3 has 3-h strength of about 3 MPa and thermal conductivity of about 0.08 W/mK.